Endovascular image-guided sampling of tumor-draining veins provides an enriched source of oncological biomarkers - Tamrazi, Anobel; Sundaresan, Srividya; Gulati, Aishwarya; Tan, Frederick J.; Wadhwa, Vibhor; Bartlett, Bjarne R.; Diaz, Luis A. Jr. (Frontiers in Oncology, 2023)
Introduction Circulating tumor-derived biomarkers can potentially impact cancer management throughout the continuum of care. This small exploratory study aimed to assess the relative levels of such biomarkers in the tumor-draining vascular beds in patients with solid tumors compared to levels in their peripheral veins. Methods Using an endovascular image-guided approach, we obtained blood samples from peripheral veins and other vascular compartments–including the most proximal venous drainage from solid tumors–from a set of nine oncology patients with various primary and metastatic malignancies. We then interrogated these samples for a panel of oncological biomarkers, including circulating tumor cells (CTCs), exosome-derived microRNAs (miRNAs), circulating tumor DNA (ctDNA) mutations, and certain cancer-related proteins/biochemical markers. Results We found substantially higher levels of CTCs, certain miRNAs, and specific ctDNA mutations in samples from vascular beds closer to the tumor compared with those from peripheral veins and also noted that some of these signals were altered by treatment procedures. Discussion Our results indicate that tumor-proximal venous samples are highly enriched for some oncological biomarkers and may allow for more robust molecular analysis than peripheral vein samples.